2017
DOI: 10.18632/oncotarget.21739
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and critique of circulating miRNAs as biomarkers of stage I-II non-small cell lung cancer

Abstract: Selected circulating microRNAs (miRNAs) have been suggested for non-invasive screening of non-small cell lung cancer (NSCLC), however the numerous proposed miRNA signatures are inconsistent.Aiming to identify miRNAs suitable specifically for stage I-II NSCLC screening in serum/plasma samples, we searched the databases “Pubmed”, “Medline”, “Scopus”, “Embase” and “WOS” and systematically reviewed the publications reporting quantitative data on the efficacy [sensitivity, specificity and/or area under the curve (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 93 publications
0
53
0
Order By: Relevance
“…Compared to previous reviews, we employed a broader inclusion criterion by including all histological types of LC cases, and we focused on studies conducted in Western populations in order to reduce a primary source of heterogeneity in miRNAs profiles. Although previous reviews have reported tremendous heterogeneity in included studies and inconsistency in LC‐related miRNA markers, very few reviews explored the sources of the heterogeneity . We comprehensively addressed heterogeneity from multiple perspectives, including study populations, biological sample types and processing, methodology in miRNA detection, and data normalization and analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to previous reviews, we employed a broader inclusion criterion by including all histological types of LC cases, and we focused on studies conducted in Western populations in order to reduce a primary source of heterogeneity in miRNAs profiles. Although previous reviews have reported tremendous heterogeneity in included studies and inconsistency in LC‐related miRNA markers, very few reviews explored the sources of the heterogeneity . We comprehensively addressed heterogeneity from multiple perspectives, including study populations, biological sample types and processing, methodology in miRNA detection, and data normalization and analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our review suggests that circulating miRNAs have great potential to be used as markers for LC detection and may be promising candidates for general cancer screening. Compared to previous reviews, 39,[58][59][60][61][62][63][64][65] we employed a broader inclusion criterion by including all histological types of LC cases, and we focused on studies conducted in Western populations in order to reduce a primary source of heterogeneity in miRNAs profiles. Although previous reviews have reported tremendous heterogeneity in included studies and inconsistency in LC-related miRNA markers, very few reviews explored the sources of the heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In lung cancer, low expression of the circulating miRNA‐34 family was associated with clinicopathological status and poor progression‐free and overall survival of NSCLC patients . miR‐223, miR‐20a, miR‐448, and miR‐145, as serum/plasma miRNA signatures, have shown high sensitivity (>80%), whereas another panel including miR‐628‐3p, miR‐29c, miR‐210, and miR‐1244 have shown high specificity (>90%) to stage I‐II NSCLC samples . Although several circulating miRNAs have been found to be associated with NSCLC, to date, their functional relevance in NSCLC has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…18 miR-223, miR-20a, miR-448, and miR-145, as serum/plasma miRNA signatures, have shown high sensitivity (>80%), whereas another panel including miR-628-3p, miR-29c, miR-210, and miR-1244 have shown high specificity (>90%) to stage I-II NSCLC samples. 19 Although several circulating miRNAs have been found to be associated with NSCLC, to date, their functional relevance in NSCLC has not been well characterized. Thus, a better understanding of the cellular functions of circulating miRNAs in NSCLC is warranted and may inform treatment responses.…”
mentioning
confidence: 99%